A qualitative exploration of perceptions and experiences of contraceptive use, abortion and post-abortion family planning services (PAFP) in three provinces in China - Yan Che; Esther Dusabe-Richards; Shangchun Wu; Yi Jiang; Xiaojing Dong; Jian Li; Wei-Hong Zhang; Marleen Temmerman; Rachel Tolhurst; INPAC group (BMC, 2017)
Abstract Background The INPAC project aims to evaluate the effectiveness of integrated post-abortion family planning (PAFP) services into existing hospital based abortion services in China. A qualitative study was conducted in three provinces to contribute to developing effective PAFP services through understanding influences on contraceptive use, experiences of abortion and existing PAFP, and their effect on future contraceptive practices from the perspective of users, in the context of social and institutional change. Methods Twenty-nine in-depth interviews (IDIs) were undertaken with women who had experienced abortion between 1 and 6 months prior to interview, recruited from three urban and two rural facilities in each province. Thirteen IDIs were also conducted with male partners. Six focus group discussions (FGDs) were carried out with community members from different social groups, including unmarried and married women and men, urban residents and rural-to-urban migrants. Results Social networks and norms are important in shaping attitudes and behaviour towards abortion and contraception. Widespread concerns were expressed about side-effects, reliability and effects on future fertility of some modern contraceptives. The combination of limited information and choices and a lack of person-centred counselling in PAFP with anxieties about side effects underlies the widespread use of unreliable methods. Gendered power relations significantly influence contraceptive (non)use, with several examples illustrating women's relative lack of power to decide on a method, particularly in the case of condoms. Although the availability of contraceptive information from respected providers can offer impetus for individual behaviour change, social distance from providers reduces opportunities for clients to discuss their difficulties regarding contraceptive use; particularly, but not exclusively for young, unmarried clients. Conclusions Increased access to non-commercial, reliable information on contraceptive methods is needed. PAFP services must go beyond simple information provision to ensure that providers take a more person-centred approach, which considers the most appropriate method for individual clients and probes for the underlying influences on contraceptive (non)use. More sensitive reflection on gender norms and relationships is required during counselling and, where women choose this, efforts should be made to include their male partners. Specific attention to provider positionality and skills for counselling young, unmarried clients is needed.